2013
DOI: 10.1111/jfr3.12034
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐scale reliability analysis of the flood defence infrastructure within the Taihu Basin, China

Abstract: The Taihu Basin is home to some of the most economically active and populous cities in China, including Shanghai. The Basin lies in the coastal delta of the Yangtze River and is defended from frequent flooding by a complex system of flood control infrastructure (including dikes, numerous large sluice gates and pumping stations). Flood risk in the Basin is closely related to the reliability of the flood defences. The information available to support system reliability analysis is however limited. A simplified d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…With this level of concern about the safety of flood control infrastructure, there has been significant research to investigate the resilience of flood control infrastructure in different CMDN. These studies tend to approach the problem from slightly different dimensions, including through stability assessment (Chen, Cheng, and Yang 2006;Shi and Kong 2016;Yang et al 2006), reliability analysis (Jiabi et al 2013), capability assessment (Zhu et al 2011), vulnerability assessment (Ogie et al 2016;, deformation assessment (Pei et al 2010) and performance assessment (Gilbuena et al 2013a).…”
Section: Resilience Of Flood Control Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…With this level of concern about the safety of flood control infrastructure, there has been significant research to investigate the resilience of flood control infrastructure in different CMDN. These studies tend to approach the problem from slightly different dimensions, including through stability assessment (Chen, Cheng, and Yang 2006;Shi and Kong 2016;Yang et al 2006), reliability analysis (Jiabi et al 2013), capability assessment (Zhu et al 2011), vulnerability assessment (Ogie et al 2016;, deformation assessment (Pei et al 2010) and performance assessment (Gilbuena et al 2013a).…”
Section: Resilience Of Flood Control Structuresmentioning
confidence: 99%
“…Another study in Shanghai focused on the reliability of flood control infrastructure such as dikes, sluice gates and pumping stations (Jiabi et al 2013). This study combines hydraulic simulation, expert judgement and knowledge of the design and condition of the flood defences to assess their performance and probability of failure when subjected to a range of loading conditions, such as river water level.…”
Section: Resilience Of Flood Control Structuresmentioning
confidence: 99%
“…Outside of the Netherlands, other countries have also made progress in developing methods and tools for assessing risks and reliability of flood defence systems, for example, in the UK (Hall et al, ), United States (USACE, ) and in the Shanghai region in China (Jiabi et al, ). Overall, it can be observed that the insights from risk and reliability analyses are now at a stage that they can be more directly applied in policy making (e.g., safety standards) and the design and management of flood defences (Schweckendiek, ).…”
Section: Basic Principles Of the Risk‐based Approachmentioning
confidence: 99%
“…Most research on Taihu Basin were focused on hydrological simulation (Liu et al, 2013), flood risk management (Xie et al, 2013;Gong and Lin, 2008), water quality Yu et al, 2007;W. Li et al, 2013;Wang et al, 2014) and ecological problems.…”
Section: Introductionmentioning
confidence: 99%